Assessment of Spirometric Interpretation Methods: A Comparison between Percent Predicted and GLI 2012 among Workers in the Silver Industry - Helina Helmy; Suami Indarwati; Ahkmad Fikri; Tati Baina Gultom; Agus Sutopo (Lembaga Publikasi Ilmiah Nusantara, 2026)
Background: Occupational exposure to fine particulate matter (PM₂.₅) in small-scale silver industries increases the risk of respiratory impairment. Spirometry is widely used to assess lung function, but differences in interpretation methods may affect diagnostic accuracy. The conventional percent predicted (%Pred) method is still commonly applied, although the Global Lung Function Initiative (GLI) 2012 recommends a Z-score–based approach. Objective: This study compared lung function classification using the %Pred method and the GLI 2012 Z-score approach among silver industry workers. Methods: This analytical cross-sectional study involved 33 workers from large-scale and home-based silver industries. Spirometry measured forced expiratory volume in one second (FEV₁), forced vital capacity (FVC), and FEV₁/FVC ratio. Lung function was classified using both %Pred and GLI 2012 methods. Differences and agreement were analyzed using the McNemar test and Cohen’s Kappa. Results: The GLI 2012 method detected a higher proportion of restrictive impairment (36.4%) than the %Pred method (21.2%). Six workers (18.2%) were reclassified from normal (%Pred) to abnormal (GLI). A significant difference was found between methods (p = 0.041), with moderate agreement (κ = 0.586). No obstructive pattern was identified. Conclusion: The GLI 2012 Z-score method is more sensitive in detecting restrictive lung impairment than the %Pred approach. The %Pred method may underestimate abnormalities. Adoption of GLI-based interpretation can improve accuracy in occupational respiratory assessment.